METHOD OF THE PROTECTED STORAGE OF MEDICAL DATA, BASED ON THE RELATIONAL DATABASE AND BLOCKCHAIN - Baryshev, Yuriy; Lanova, Vladyslava (Scientific Works of Vinnytsia National Technical University, 2024)
The paper contains the analysis of the known practices of using the blockchain technology in the health care sphere. Structures of the data storage organization have been considered. Tasks, emerging in the process of blockchain technology application for storage of the confidential information in critical systems, such as, medicine are determined. The paper contains the analysis of the system of creation of the electronic medical referrals, used in Ukraine. Method of medical data storage, based on the usage of the hybrid storage environment, based on the blockchain and relational data base has been suggested. The basis of the method is the classification of the data according to the requirements regarding the security of the information properties, the reflection of which these data are, for the determination of their storage method. To prove the usability of the method the example of its realization for the problems in the sphere of family medicine, namely, the process of issuing of electronic referrals for the additional health examination by the specialists, is presented. The results of projecting the relational data base for this subject field are shown, within the limits of this projecting main essences and attributes of this data base are determined. The analysis of the requirements, regarding the security of these data has been carried out, on the base of the analysis their classification according to the suggested method has been performed. For storage of the data in the blockchain, corresponding smart-contract has been developed, it provides the interface for the access of the data, which require improved integrity security, accessibility and combination of these properties. Programming module for combining the relational data base and blockchain to reflect the data for clients programs incapsulated, irrespective of the actual place of their storage, has been developed. Mechanism for improving the security of the data integrity in the relational data base at the expense of their verification in the blockchain, without disclosing the content of these data has been suggested. Perspectives of further research are defined.